Compressive behaviour of sodium and potassium activators synthetized fly ash geopolymer at elevated temperatures: A comparative study - Hosan, A.; Haque, S.; Shaikh, Faiz (2016)
This paper presents the effects of sodium and potassium based activators on compressive strengths and physical changes of class F fly ash geopolymer exposed to elevated temperatures. Samples were heated at 200 °C, 400 °C, 600 °C and 800 °C to evaluate the residual compressive strength after 28 days of curing. The fly ash geopolymer were synthesized with combined sodium silicate and sodium hydroxide solutions and potassium silicate and potassium hydroxide solutions by varying mass ratios of Na 2 SiO 3 /NaOH and K 2 SiO 3 /KOH of 2, 2.5 and 3. Results show significant improvement is compressive strength in the case of Na 2 SiO 3 /NaOH ratio of 3 than 2 and 2.5, where the residual compressive strengths are increased up to 600 °C. Better results on the geopolymer synthesized with potassium based activators are obtained where the residual compressive strength up to 600 °C are much higher than their sodium based counterparts. It is also found that the fly ash geopolymer synthesized with potassium based activators is more stable at elevated temperatures than its sodium based counterparts in terms of higher residual compressive strengths, lower mass loss, lower volumetric shrinkage and lower cracking damage. X-ray diffraction (XRD) and thermogravimetric analysis (TGA) results of sodium and potassium activator synthesized fly ash geopolymer also corresponds to the measured residual compressive strengths.